Tradisi perayaan satu suro pada masyarakat jawa perspektif Maqashid Syariah: Bahasa Indonesia - Fitriani, Desi (Maliki Interdisciplinary Journal, 2024)
The tradition of one suro is an integral part of the life and identity of the Javanese people. The Satu Suro tradition is interpreted as a moment for introspection, cleansing oneself physically and mentally, and giving thanks to God. In the Satu Suro tradition, it describes how Islamic values ​​and Javanese culture influence each other and shape people's identities. Spiritual and cultural values ​​in the one suro tradition are important for maintaining the continuity of the tradition by ensuring compatibility with religious teachings. The aim of this research is to provide a comprehensive understanding of the Satu Suro tradition and relate it to cultural values, religion, and Islamic principles. This study uses qualitative analysis to analyze the cultural values ​​contained in the tradition, and to relate it to religious principles and Maqasid Sharia. The technique in collecting data for this article uses literature study by collecting data through books, scientific papers, and mass media. The object of this research is the Satu Suro tradition in the context of Javanese society. The results of the study show that the tradition of one suro remains in accordance with Islamic religious teachings and does not conflict with the principles of Maqasid Sharia.